Vertical phase separation in small molecule: polymer blend organic thin film transistors can be dynamically controlled - Zhao,K; Wodo,O; Ren,D; Khan,HU; Niazi,MR; Hu,H; Abdelsamie,M; Li,R; Li,EQ; Yu,L; Yan,B; Payne,MM; et al. (Advanced Functional Materials, 2016)
Blending of small-molecule organic semiconductors (OSCs) with amorphous polymers is known to yield high performance organic thin film transistors (OTFTs). Vertical stratification of the OSC and polymer binder into well-defined layers is crucial in such systems and their vertical order determines whether the coating is compatible with a top and/or a bottom gate OTFT configuration. Here, we investigate the formation of blends prepared via spin-coating in conditions which yield bilayer and trilayer stratifications. We use a combination of in situ experimental and computational tools to study the competing effects of formulation thermodynamics and process kinetics in mediating the final vertical stratification. It is shown that trilayer stratification (OSC/polymer/OSC) is the thermodynamically favored configuration and that formation of the buried OSC layer can be kinetically inhibited in certain conditions of spin-coating, resulting in a bilayer stack instead. The analysis reveals here that preferential loss of the OSC, combined with early aggregation of the polymer phase due to rapid drying, inhibit the formation of the buried OSC layer. The fluid dynamics and drying kinetics are then moderated during spin-coating to promote trilayer stratification with a high quality buried OSC layer which yields unusually high mobility >2 cm2 V−1 s−1 in the bottom-gate top-contact configuration.